Resilience of English vowel perception across regional accent variation. Issue 1 (17th July 2018) - Shaw, Jason A.; Best, Catherine T.; Docherty, Gerard; Evans, Bronwen G.; Foulkes, Paul; Hay, Jennifer; Mulak, Karen E.
Abstract : In two categorization experiments using phonotactically legal nonce words, we tested Australian English listeners' perception of all vowels in their own accent as well as in four less familiar regional varieties of English which differ in how their vowel realizations diverge from Australian English: London, Yorkshire, Newcastle (UK), and New Zealand. Results of Experiment 1 indicated that amongst the vowel differences described in sociophonetic studies and attested in our stimulus materials, only a small subset caused greater perceptual difficulty for Australian listeners than for the corresponding Australian English vowels. We discuss this perceptual tolerance for vowel variation in terms of how perceptual assimilation of phonetic details into abstract vowel categories may contribute to recognizing words across variable pronunciations. Experiment 2 determined whether short-term multi-talker exposure would facilitate accent adaptation, particularly for those vowels that proved more difficult to categorize in Experiment 1. For each accent separately, participants listened to a pre-test passage in the nonce word accent but told by novel talkers before completing the same task as in Experiment 1. In contrast to previous studies showing rapid adaptation to talker-specific variation, our listeners' subsequent vowel assimilations were largely unaffected by exposure to other talkers' accent-specific variation.